Reinventando o Brasil : Manoel Bomfim e a crítica à historiografia brasileira - Tonon, Marina Rodrigues [UNESP] (2014)
The History of Historiography has been devoted in recent decades to the study of the fundamentals of writing the history of various authors. Inserted into this tradition, this study aims to understand the writing of history Manoel Bomfim. An intellectual, author of a vast bibliography on various subjects and in their studies devoted to the history presents a vision, considered by many commentators, peculiar and even rebellious. From this and worried about playing some nuances of the historical culture of the early twentieth century, we intend to investigate the grounds and procedures used by Bomfim in his writing of history, paying particular attention to the definition of history built up by this author, as well as the vision of the Brazilian past and the election of subjects that are part of your writing history